Clinicopathological Role of Adiponectin in Preeclampsia: Linkage with Placental Function and Maternal Health: Clinical-pathology of Adiponectin in Preeclampsia: Placental and Maternal Outcomes - Adam, Mohammedelfateh; Khan, Sarfaraz; Zia, Memona; Iftikhar, Anum; Sherazi, Sajid Hussain; Ahsan, Naveed; Haq, Ehsan Ul (Pakistan Journal of Health Sciences, 2024)
Preeclampsia is a hypertensive, multisystem disease in pregnancy, associated with dysfunction of the placenta. Emerging studies point toward the possibility that adiponectin, a hormone with anti-inflammatory and vasodilator properties, may contribute to the development of preeclampsia. Objectives: To systematically review the role of adiponectin in the pathophysiology of preeclampsia with limited evidence on the role of placental gene expression, providing clinicopathological insights into its role in maternal and fetal health. Methods: A comprehensive literature search was conducted across PubMed, Science Direct, and Google Scholar for articles published between 2017 and 2024. Included studies explored the relationship between Adiponectin levels and preeclampsia in relevance to placental pathology, and hormonal levels. Studies analyzed adiponectin's role in modulating insulin resistance, hypertension, placental growth, and vascular health in preeclampsia. Data from multiple regions, including Asia, Europe, and America, provided global perspectives. Results: An association between reduced adiponectin levels and increased severity of preeclampsia and its potential role in impaired placental physiology and adverse pregnancy outcomes were reviewed. Conclusions: It was concluded that adiponectin plays a crucial role in the pathophysiology of preeclampsia, affecting both maternal health and placental function. Understanding these mechanisms may offer insights for therapeutic interventions in managing preeclampsia and improving fetal outcomes.